Optimalisasi Penataan Lumbung Mataraman dalam Mendukung Kawasan Wisata Edukasi Terpadu Padukuhan Ngalian, Desa Widodomartani - Yudhistira Saraswati; Rian Adetiya Pratiwi (Institut Pertanian Bogor, 2024)
Lumbung Mataraman is a program initiated by the Provincial Government of Daerah Istimewa Yogyakarta to fulfill the community's food needs through home gardens. This program is also directed to become an alternative tourist destination with local potential. Lumbung Mataraman is managed by Women Farmers Group (Kelompok Wanita Tani or KWT) Mekar and as part of Empon-empon Village. Location of the activities takes place in Ngalian, Widodomartani Village, D.I. Yogyakarta. The arrangement of Lumbung Mataram aims to arrange the layout of the land according to its function and enhance its appearance. The output is Lumbung Mataram KWT Mekar site plan. The site plan creation process follows landscape design procedures involving site inventory or collecting existing data; analysis of site potential and problems; synthesis or problem-solving; and the development of design concepts and design. The rearrangement of Lumbung Mataraman remains the same as its existing function but focuses on maximizing the utilization of existing potential and adding aesthetic value. The results of this activity are to optimize the function of Lumbung Mataram as a provider of food needs and to support the integrated educational tourism area.